2018
DOI: 10.2147/jpr.s154002
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis: pathophysiology and current treatment modalities

Abstract: For decades, multiple attempts to fully understand knee osteoarthritis pathophysiology and natural history have been attempted. Despite the extensive amount of research regarding this topic, there are still marked controversies. This multifactorial condition gets influenced by local, systemic, and external factors and its progression and/or response to treatments widely varies from patient to patient. Multiple therapies have been studied in the past, low impact physical activity seems to be supported by all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
352
0
31

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 393 publications
(388 citation statements)
references
References 58 publications
5
352
0
31
Order By: Relevance
“…Osteoarthritis is the most usual form of arthritis and one of the leading causes of disability. OA is a chronic and low‐grade inflammation, involving mainly innate immune mechanisms (Mora, Przkora, & Cruz‐Almeida, ). It is well known that inflammatory mediators associated with OA include cytokines, chemokines, growth factors, adipokines, prostaglandins, leukotrienes, nitric oxide, and neuropeptides (Robinson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoarthritis is the most usual form of arthritis and one of the leading causes of disability. OA is a chronic and low‐grade inflammation, involving mainly innate immune mechanisms (Mora, Przkora, & Cruz‐Almeida, ). It is well known that inflammatory mediators associated with OA include cytokines, chemokines, growth factors, adipokines, prostaglandins, leukotrienes, nitric oxide, and neuropeptides (Robinson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis is the most usual form of arthritis and one of the leading causes of disability. OA is a chronic and low-grade inflammation, involving mainly innate immune mechanisms (Mora, Przkora, & Cruz-Almeida, 2018). It is well known that inflammatory mediators associated with OA include cytokines, chemokines, growth factors, Creatinine (mg/dl) Pretreatment 0.7 ± 0.1 0.7 ± 0.2 0.7 ± 0.1 p = 0.24 95% (CI) 0.7, 0.8 0.6, 0.7 0.6, 0.7 Postreatment 0.7 ± 0.2 0.7 ± 0.2 0.6 ± 0.2 p = 0.03 95% (CI) 0.7, 0.8 0.6, 0.8 0.6, 0.7 p value 0.45 0.67 0.04* adipokines, prostaglandins, leukotrienes, nitric oxide, and neuropeptides (Robinson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the programme design, we agree with Dr Kaijiwar and his colleagues that incorporating knowledge of BPSD in the context of OA into the intervention may be useful and needs further investigation in future study.Self-management and regular exercise are the critical factors in knee OA management. 3,4 Considering outcomes measures of our programme, we measure their in-home exercise adherence by asking the caregivers about the PWD spending how much time on exercise per week. The results showed that the total duration of exercise per week in IG increased statistically significant (P < .022) after the intervention.And this result will be published elsewhere.In addition, in most of our caregiver participants, the full-time domestic helpers were delivering the home exercises.…”
mentioning
confidence: 99%
“…Self-management and regular exercise are the critical factors in knee OA management. 3,4 Considering outcomes measures of our programme, we measure their in-home exercise adherence by asking the caregivers about the PWD spending how much time on exercise per week. The results showed that the total duration of exercise per week in IG increased statistically significant (P < .022) after the intervention.…”
mentioning
confidence: 99%